Cripps Mission (March, 1942) In India: Why Did It Fail? Evaluating the Failure of the Cripps Mission in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The British Government after careful consideration sentCripps, a brilliant lawyer, an avowed socialist, an intimate friend of Nehru toIndia. Cripps had long been a serious student of the Indian question and hadthe reputation of being favorably disposed to Indian aspirations. For some timethe United States had been pressing Britain to satisfy Indian demands forSelf-government.